2021
DOI: 10.3390/s21134535
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Neural Network Approaches for Estimating Joint Angles and Moments from Inertial Measurement Units

Abstract: The application of artificial intelligence techniques to wearable sensor data may facilitate accurate analysis outside of controlled laboratory settings—the holy grail for gait clinicians and sports scientists looking to bridge the lab to field divide. Using these techniques, parameters that are difficult to directly measure in-the-wild, may be predicted using surrogate lower resolution inputs. One example is the prediction of joint kinematics and kinetics based on inputs from inertial measurement unit (IMU) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 31 publications
1
47
0
Order By: Relevance
“…Mundt et al also compared LSTM and feedforward neural networks (FFNN) performance on time-normalized gait cycle input data and achieved better performance using the FFNN. In a more recent study, the same group compared the performance of three common neural networks for joint kinematic and kinetic predictions, finding that convolutional neural networks achieved higher accuracy than LSTM networks but required additional data processing steps that would hinder applications working in real time [ 46 ]. For the current study, we evaluated multiple network architectures [ 10 , 22 , 26 , 47 ] and found the BiLSTM model had the most robust performance.…”
Section: Discussionmentioning
confidence: 99%
“…Mundt et al also compared LSTM and feedforward neural networks (FFNN) performance on time-normalized gait cycle input data and achieved better performance using the FFNN. In a more recent study, the same group compared the performance of three common neural networks for joint kinematic and kinetic predictions, finding that convolutional neural networks achieved higher accuracy than LSTM networks but required additional data processing steps that would hinder applications working in real time [ 46 ]. For the current study, we evaluated multiple network architectures [ 10 , 22 , 26 , 47 ] and found the BiLSTM model had the most robust performance.…”
Section: Discussionmentioning
confidence: 99%
“…The NN had the same structure as the NN used in the LSTM model. The CNN used the structure used in the precedent studies [ 20 , 21 , 22 , 23 ]. The convolution layer used 8 sets of 15 × 1 × 1 three-dimensional matrices as a kernel, and the stride was composed of a 1 × 1 × 1 matrix.…”
Section: Methods and Design Of The Proposed Systemmentioning
confidence: 99%
“…The acceleration sensor, the angular velocity sensor, the height sensor, and the EMG sensor are used to measure the current movement, running, walking, and climbing stairs [ 5 , 6 , 7 , 8 , 9 , 10 ]. Based on these studies, research on motion measurement using artificial intelligence is also being conducted, which greatly contributes to the development of the healthcare and game industry [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Research related to motorcycle accidents is also increasing.…”
Section: Introductionmentioning
confidence: 99%
“…The LSTM cell has a more complex structure and was shown to better handle long-term dependencies within the data [33]. LSTM networks have been proposed to solve problems dealing with wearable inertial sensor data, e.g., in the area of odometry [24,25], pedestrian dead reckoning [26], kinematics [15,31,34,35], attitude estimation [32,36], fall risk assessment [30], activity recognition [37,38], among others.…”
Section: Network Architecturementioning
confidence: 99%
“…The network architecture used in this study was inspired by past works in related fields, namely, in [25], [34] or [35]. In kinematics, in particular, LSTM networks were proposed to predict multidimensional sequences of kinematic variables-e.g., joint angles and moments-from multidimensional sequences of inertial sensor data-acceleration and angular rotation [34,35]. Using a similar approach, we proposed to predict multidimensional trajectories from multidimensional IMU data.…”
Section: Problem Formulationmentioning
confidence: 99%